Risk factors for hematogenous complications of intravascular catheter-associated Staphylococcus aureus bacteremia. - Fowler, V; Justice, A; Moore, C; Benjamin, D; Woods, C; Campbell, S; Reller, L; Corey, G; Day, N; Peacock, S (2005)
BACKGROUND: The role of both host and pathogen characteristics in hematogenous seeding following Staphylococcus aureus bacteremia is incompletely understood. METHODS: Consecutive patients with intravascular catheter-associated Staphylococcus aureus bacteremia were prospectively recruited over a 91-month period. The corresponding bloodstream isolates were examined for the presence of 35 putative virulence determinants. Patient and bacterial characteristics associated with the development of hematogenous complications (HCs) (i.e., septic arthritis, vertebral osteomyelitis, or endocarditis) were defined. RESULTS: HC occurred in 42 (13%) of 324 patients. Patient characteristics at diagnosis that were associated with HC included community onset (relative risk [RR], 2.25; 95% confidence interval [CI], 1.24-4.07; P=.007), increased symptom duration (odds ratio for each day, 1.14; 95% CI, 1.06-1.2; P<.001), presence of a long-term intravascular catheter or noncatheter prosthesis (RR, 4.02; 95% CI, 1.74-9.27; P<.001), hemodialysis dependence (RR, 3.84; 95% CI, 2.08-7.10; P<.001), and higher APACHE II score (P=.02). Bacterial characteristics included sea (RR, 2.03; 95% CI, 1.16-3.55; P=.011) and methicillin-resistant S. aureus (MRSA) (RR, 2.09; 95% CI, 1.19-3.67; P=.015). Subsequent failure to remove a catheter was also associated with HC (RR, 2.28; 95% CI, 1.22-4.27; P=.011). On multivariable analysis, symptom duration, hemodialysis dependence, presence of a long-term intravascular catheter or a noncatheter device, and infection with MRSA remained significantly associated with HC. CONCLUSIONS: This investigation identifies 4 host- and pathogen-related risk factors for hematogenous bacterial seeding and reaffirms the importance of prompt catheter removal.